Auditing the use and assessing the clinical utility of microscopy as a point-of-care test for Neisseria gonorrhoeae in a Sexual Health clinic. (February 2018) - Mensforth, Sarah; Thorley, Nicola; Radcliffe, Keith
We assessed whether urethral microscopy was performed as per clinic protocol for male clinic attendees reporting contact with Neisseria gonorrhoeae (GC), urethral symptoms or given a diagnosis of epididymo-orchitis (EO) over a 12-month period (9732 patients). Prevalence of gonorrhoea in the contacts, urethral symptoms and EO groups was 50, 12.7 and 1.6%, respectively. Microscopy was performed reliably for contacts (96%), those with discharge/dysuria with evidence of urethritis on examination (98%), but not those with EO (43%). We explored the clinical utility of microscopy as a point-of-care test for identifying urethral GC in each subgroup, using the APTIMA Combo 2 CT/GC nucleic acid amplification test as the comparator (1710 patients). Sensitivity of microscopy for each subgroup was good; there was no statistical difference between subgroup sensitivity using Fisher's exact test. Microscopy is valuable to ensure prompt diagnosis and contact tracing. All GC contacts were treated 'epidemiologically'; however, half of GC contacts did not have GC. Microscopy identified the majority of GC cases, including amongst contacts (71% of heterosexual contacts, 66% of contacts reporting sex with men). We propose that epidemiological treatment for GC contacts should be reconsidered on the grounds of antibiotic stewardship, favouring use of microscopy to guide treatment decisions.